Respiratory tract antimicrobial peptides more effectively killed multiple methicillin-resistant Staphylococcus aureus and nontypeable Haemophilus influenzae isolates after disruption from biofilm residence - Nikola Kurbatfinski; Joseph A. Jurscisek; Kathryn Q. Wilbanks; Steven D. Goodman; Lauren O. Bakaletz (Microbiology Spectrum)
ABSTRACT Bacteria newly released (NRel) from biofilm residence via multiple methodologies are commonly significantly more sensitive to antibiotics. We’ve induced NRel with this phenotype after incubation of biofilms formed by diverse human pathogens with an epitope-targeted monoclonal antibody directed at protective domains within bacterial DNABII proteins that provide structural support to the eDNA-dependent biofilm matrix. The observed heightened sensitivity was due, in part, to increased NRel membrane permeability. In three animal models of human biofilm-mediated infections, this monoclonal induced biofilm disruption with rapid concomitant bacterial clearance and disease resolution in the absence of any co-delivered antibiotic, which suggested a key role of innate immune effectors. Recently, we showed that NRel of the respiratory pathogen nontypeable Haemophilus influenzae (NTHI), as mediated by the DNABII-directed monoclonal, are also highly vulnerable to killing by human polymorphonuclear neutrophils (PMNs). Here, we extended these observations to show that the transient, yet highly vulnerable anti-DNABII NRel phenotype of three isolates of both NTHI and methicillin-resistant Staphylococcus aureus (MRSA) included significant sensitivity to killing by three antimicrobial peptides commonly expressed within the respiratory tract or by PMNs (e.g., human β-defensins 1 and 3 as well as the cathelicidin, LL-37). We envision induction of the NRel phenotype by delivery of this monoclonal antibody to patients with recalcitrant biofilm-mediated diseases to provide greatly improved medical management. Ideally, clearance of NRel will be mediated by innate immune effectors of an immunocompetent host or, if needed, by co-delivered traditional antibiotics, which are canonically ineffective against biofilm-resident bacteria but would be highly effective against NRel.IMPORTANCEPathogenesis of most common chronic and/or recurrent bacterial diseases (e.g., middle ear infections, urinary tract infections, rhinosinusitis, among others) can be attributed to biofilms that are canonically highly resistant to both immune effectors and antibiotics. If we treat biofilms formed by diverse human pathogens with a targeted monoclonal antibody directed at protective domains of bacterial DNA-binding proteins integral to the structural stability of the eDNA-rich biofilm matrix, they are rapidly disrupted with concomitant release of the resident bacteria. These newly released (NRel) bacteria are transiently significantly more sensitive to killing by both traditional antibiotics and human PMNs, and herein, we showed that they are also more readily killed by antimicrobial peptides. Clinically, we hope to leverage this understanding of the NRel phenotype for better medical management of these challenging infections, as well as perhaps even limit or eliminate further contribution to the global antimicrobial resistance ’pandemic’.